Effect of thiabendazole on gains of stockers grazing 50% endophyte fungus-infected, tall fescue pastures - F. Brazle (Kansas Agricultural Experiment Station Research Reports, 1986)
Thiabendazole (TBZ®) wormer pellets were added to either a mineral or grain mix in two experiments with steers grazing 50% endophyte fungus-infected, tall fescue pastures. Research from other stations has suggested that TBZ® partially overcomes the toxicity of endophyte fungus. In our experiments, steers received .2 g of TBZ® per 100 lb body weight per day, but daily gain was not improved during the grazing period.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Thiabendazole; Stockers; Fescue; Endophyte